2018
DOI: 10.21475/ajcs.18.12.06.pne884
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sweet potato cultivars planted harvested at different times of two seasons

Abstract: This study aimed at adapting harvest time of different potato cultivars in two seasons during the year. Two experiments were conducted: one in the rainy season and another in the dry period. Two production factors were studied in experiments using a splitplot design in a complete randomized block design. The first factor (including 3 sweet potato cultivars: ESAM 1, Paraná and Mãe de Família) was assigned to the plots. The second factor (harvest time: 90, 105, 120, 135 and 150 days after planting) was assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Deus (2019), evaluating doses of P (40, 80, 120 and 160 kg ha -1 of P 2 O 5 ) as sweet potato, did not identify variation in the content of total soluble sugars with the doses of P 2 O 5 , presenting an average of 4.80%. However, Albuquerque et al (2018) observed variation in the content of soluble solids and total soluble sugars among sweet potato cultivars.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Deus (2019), evaluating doses of P (40, 80, 120 and 160 kg ha -1 of P 2 O 5 ) as sweet potato, did not identify variation in the content of total soluble sugars with the doses of P 2 O 5 , presenting an average of 4.80%. However, Albuquerque et al (2018) observed variation in the content of soluble solids and total soluble sugars among sweet potato cultivars.…”
Section: Resultsmentioning
confidence: 82%
“…Total soluble solids (%) The cultivar Água Morna showed greater firmness in the root pulp among the evaluated cultivars (Table 2), while the cultivar BRS Gema de Ovo showed the lowest values, demonstrating that this parameter is influenced by genetics. Albuquerque et al (2018) found variation in root firmness among sweet potato cultivars and associated this behavior with the starch content. Cultivars with a higher starch content tend to have greater root firmness and cultivars with a lower starch content consequently have less firmness.…”
Section: Resultsmentioning
confidence: 91%
“…Their content did not exceed 6% which could indicate the freshness of the SP tubers used in the present study. In fact, delayed harvesting time and storage increase significantly total soluble sugar content of sweet potato (Adu-Kwarteng et al, 2014;Albuquerque et al, 2018). The starch content of the different SP flours (31% -61%) was in the range reported by Jangchud et al (2003) (36.6-75.0%) but lower compared to other studies (Olatunde et al, 2019).…”
Section: Proximate Compositionmentioning
confidence: 61%
“…Studied site spatial factors, soil characteristics, and diversity indices variations observed could explain the response in the proximal composition of the evaluated species, where the sites showed neutral pH. According to de Albuquerque et al ( 67 ) and Misra and Tyler ( 68 ), the pH and nutrient availability at these sites were directly controlled by the soil texture and water availability. The neutral soil pH additionally the availability and uptake of nutrients from the soil, that aid in increasing nutritional value of a plant species ( 69 ).…”
Section: Discussionmentioning
confidence: 85%